2014
DOI: 10.1007/s00198-014-2875-2
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent fracture rates in a nationwide population-based cohort study with a 10-year perspective

Abstract: Patients suffering a fracture (and especially a hip fracture) have a high incidence of subsequent fracture. Fractures after the age of 50 may be considered an early warning of increased risk for future fractures in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 28 publications
0
29
1
1
Order By: Relevance
“…Incidence (per 1000 PYs) of first fracture has previously been reported among the general population for these study populations, and was as follows: hip = 4.9, wrist = 4.8, forearm = 5.9, vertebral = 1.3, humerus = 4.1, and pelvis = 0.7 (Danish Health Registries); hip = 2.23, wrist/forearm = 2.56, clinical spine = 1.98, humerus = 1.55, and pelvis = 0.04 (SIDIAP). The rate of first fracture among all‐incident oral BP users within the Danish Health Registries (55.2/1000 PYs) is comparable with previous work and would appear to be representative of Danish BP users.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Incidence (per 1000 PYs) of first fracture has previously been reported among the general population for these study populations, and was as follows: hip = 4.9, wrist = 4.8, forearm = 5.9, vertebral = 1.3, humerus = 4.1, and pelvis = 0.7 (Danish Health Registries); hip = 2.23, wrist/forearm = 2.56, clinical spine = 1.98, humerus = 1.55, and pelvis = 0.04 (SIDIAP). The rate of first fracture among all‐incident oral BP users within the Danish Health Registries (55.2/1000 PYs) is comparable with previous work and would appear to be representative of Danish BP users.…”
Section: Discussionmentioning
confidence: 59%
“…Incidence (per 1000 PYs) of first fracture has previously been reported among the general population for these study populations, (27,28) and was as follows: hip ¼ 4.9, wrist ¼ 4. (29) and would appear to be representative of Danish BP users.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 64%
“…The same relative risks were found in men and women, though the absolute risk was higher in women. This transient phenomenon will be missed in long-term follow-up studies where the pattern of risk with time is not studied [2,[19][20][21]. Several previous studies have found that a recent occurrence of fracture was a greater risk factor for subsequent fracture than a history of earlier fracture, demonstrated for vertebral fracture [6,11], hip, humeral and forearm fractures [3,6] and all fractures combined [12].…”
Section: Discussionmentioning
confidence: 98%
“…It is well established that fragility fractures increase the risk of a further fracture [1][2][3][4]. In a meta-analysis performed by Klotzbuecher et al [5], the relative risk of having a hip fracture or a vertebral fracture was approximately 2-fold higher for most types of prior fracture.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, including exposures over the long term with the same weight as recent exposures might dilute the risk associated with these exposures if only the short‐term association is present. This is likely the case for prior fractures where the risk of new fractures and risk of mortality is strongly dependent on the recency of the first fracture …”
Section: Discussionmentioning
confidence: 99%